INOVASI PERPUSTAKAAN DESA DALAM MENINGKATKAN LITERASI INFORMASI MASYARAKAT DESA BATU MILA KABUPATEN ENREKANG - Nurhasana Nurhasana; Ismaya Ismaya; Muhammad Nasrul (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2026)
This study aims to analyze the forms of innovation carried out by the Batu Mila Village Library and their impact on improving the information literacy of the village community.  This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the Batu Mila Village Library has implemented various service innovations, such as a gazebo, computer services, a display board, and educational games. Based on the data obtained, the implementation of these innovations has had a positive impact on increasing visits, community involvement in literacy activities, and the use of the library as a non-formal learning center in the village.